2020
DOI: 10.1038/s41380-020-00923-z
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic performance and prediction of clinical progression of plasma phospho-tau181 in the Alzheimer’s Disease Neuroimaging Initiative

Abstract: Whilst cerebrospinal fluid (CSF) and positron emission tomography (PET) biomarkers for amyloid-β (Aβ) and tau pathologies are accurate for the diagnosis of Alzheimer's disease (AD), their broad implementation in clinical and trial settings are restricted by high cost and limited accessibility. Plasma phosphorylated-tau181 (p-tau181) is a promising blood-based biomarker that is specific for AD, correlates with cerebral Aβ and tau pathology, and predicts future cognitive decline. In this study, we report the per… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

20
212
0
2

Year Published

2021
2021
2022
2022

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 231 publications
(234 citation statements)
references
References 47 publications
20
212
0
2
Order By: Relevance
“…The strengths of this study include the standardized collection and measurement of relevant biomarkers in both plasma and CSF—which allowed for direct comparison between biomarkers and across the two modalities—and the availability of multi-year follow-up data in a large number of participants. Our study improves in particular on previous studies linking novel plasma tau levels on their own with cognitive decline and neurodegeneration in similar populations 43,44 . Understanding the overlapping contributions of novel tau biomarkers is therefore a major contribution of our results.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…The strengths of this study include the standardized collection and measurement of relevant biomarkers in both plasma and CSF—which allowed for direct comparison between biomarkers and across the two modalities—and the availability of multi-year follow-up data in a large number of participants. Our study improves in particular on previous studies linking novel plasma tau levels on their own with cognitive decline and neurodegeneration in similar populations 43,44 . Understanding the overlapping contributions of novel tau biomarkers is therefore a major contribution of our results.…”
Section: Discussionsupporting
confidence: 83%
“…7 This has led to an increasing focus on cognitively unimpaired (CU) older individuals at risk for progression to AD dementia on the basis of biomarker evidence of brain AD pathology. 8 Studies on combinations of blood-based Aβ42/Aβ40, P-tau and NfL have reported findings on their diagnostic accuracy for the separation of AD dementia from CU individuals and patients with non-AD disorders, 11,13,17-21 but data is lacking on their performance in predicting cognitive decline and clinical progression in CU individuals. We therefore tested the usefulness of plasma Aβ42/Aβ40, P-tau217, and NfL (separately and combined) for predicting cognitive decline and clinical outcomes in CU individuals who were followed longitudinally.…”
Section: Introductionmentioning
confidence: 99%
“…In the study by Janelidze et al, [80] it was found that individuals who had abnormal baseline levels of p-tau181 had a substantially increased risk of developing AD dementia in the future (HR = 10.9, 95% CI = 5.0-24.0). In a similar manner, using the ADNI data resource [113], higher plasma p-tau181 in MCI patients (HR = 22.75, 95% CI = 9.90-52.3) and Aβ + CU individuals (HR = 3.25, 95% CI = 1.12-9.40) had a greater risk of developing AD dementia over a 48-month period. The hazard ratios (HR) observed for plasma where similar for CSF results from the same patients (MCI, HR = 37.1, 95% CI = 15.0-91.8; HR Aβ + CU = 5.4, 95% CI = 1.8-16.3) [79].…”
Section: Phase 3: Primary Aimmentioning
confidence: 89%
“…The secondary aim 4 of phase 3 is to determine a biomarker testing interval for phase 4 if repeated testing is of interest. Longitudinal measurements of plasma p-tau have revealed low intra-individual variability, which could be of potential benefit in disease-modifying trials seeking a measurable response to a therapeutic target [25,98,106,113]. However, the stability of p-tau has not been common in all studies, namely in the longitudinal evaluation of familial AD [114], which may reflect different preanalytical protocols or a difference in how p-tau is expressed in familial AD.…”
Section: Phase 3: Secondary Aimmentioning
confidence: 99%
“…The cognitive performance is a pivotal indicator in AD management and efficacy evaluation. Previous studies found plasma Aβ 1-42 [10], NfL [11, 12], and p-tau181 [3, 4, 13] were significantly different in participants with mild cognitive impairment (MCI) and AD compared with participants with normal cognition (NC). However, few studies depicted plasma biomarkers’ profiles based on the cognitive performance and compared their discrepancy during the entire course of AD.…”
Section: Introductionmentioning
confidence: 99%